2010
DOI: 10.1124/jpet.110.174151
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Pain Signals an Increase in Functional Expression of Organic Anion Transporting Polypeptide 1a4 at the Blood-Brain Barrier

Abstract: Pain is a dominant symptom associated with inflammatory conditions. Pharmacotherapy with opioids may be limited by poor blood-brain barrier (BBB) permeability. One approach that may improve central nervous system (CNS) delivery is to target endogenous BBB transporters such as organic anion-transporting polypeptide 1a4 (Oatp1a4). It is critical to identify and characterize biological mechanisms that enable peripheral pain/inflammation to "transmit" upstream signals and alter CNS drug transport processes. Our go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
156
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(158 citation statements)
references
References 41 publications
1
156
1
Order By: Relevance
“…5B). Because TGF-␤ signaling is deregulated during inflammatory pain (44,45), we assessed whether thermal pain response in Tgfbr1 cKO mice are affected after experimental inflammation induced by intraplantar carrageenan injection. We injected carrageenan into the left and vehicle into the right hind paws of 1-month-old Tgfbr1 cKO and control mice, and then we measured paw withdrawal latency at 5 and 24 h after injection.…”
Section: Decreased Cdk5 Activity and Attenuated Responses To Thermal mentioning
confidence: 99%
“…5B). Because TGF-␤ signaling is deregulated during inflammatory pain (44,45), we assessed whether thermal pain response in Tgfbr1 cKO mice are affected after experimental inflammation induced by intraplantar carrageenan injection. We injected carrageenan into the left and vehicle into the right hind paws of 1-month-old Tgfbr1 cKO and control mice, and then we measured paw withdrawal latency at 5 and 24 h after injection.…”
Section: Decreased Cdk5 Activity and Attenuated Responses To Thermal mentioning
confidence: 99%
“…16 Although not directly studied at the BBB, OATP1A2 has been shown to transport rosuvastatin in isolated human hepatocytes and atorvastatin in human embryonic kidney cells (HEK293) stably transfected with OATP1A2. 17,18 Using our in vivo model of pain/inflammation, we have shown that Oatp1a4 is a BBB transporter that can be exploited to optimize CNS delivery of opioid peptide drugs; 19 however, Oatp1a4-mediated delivery of statins across the brain microvascular endothelium under conditions of H/R has not been clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies in our in vivo inflammatory pain model showed increased BBB functional expression of Oatp1a4 only between 1 hour and 6 hours after induction of pain/inflammation. 19 Therefore, if Oatp1a4 is to be utilized for effective delivery of therapeutics (i.e., statins) for treatment of diseases with an H/R component, its functional expression must be controlled over a more desirable time course than is possible by only relying on pathophysiologic processes. This objective can be accomplished by pharmacological targeting of signaling pathways that regulate Oatp1a4 such as the transforming growth factor-b (TGF-b) system.…”
Section: Introductionmentioning
confidence: 99%
“…Both pathophysiological factors (i.e., inflammatory signaling in pain) and pharmacological factors (i.e., use of ancillary pain medications) can modulate mechanisms involved in BBB opioid transport, an effect that can cause profound changes in CNS delivery of traditional opioids (i.e., morphine, meperidine). In fact, our research group has demonstrated that painful and/ or inflammatory stimuli in the periphery can significantly change transport mechanisms for opioids at the BBB such as the drug efflux transporter P-glycoprotein (P-gp) (5) and the drug influx transporter organic anion transporting polypeptide 1a4 (6). Of particular note, we have also shown that diclofenac itself can attenuate paininduced changes in BBB transporter activity (6).…”
Section: Dear Editormentioning
confidence: 96%
“…In fact, our research group has demonstrated that painful and/ or inflammatory stimuli in the periphery can significantly change transport mechanisms for opioids at the BBB such as the drug efflux transporter P-glycoprotein (P-gp) (5) and the drug influx transporter organic anion transporting polypeptide 1a4 (6). Of particular note, we have also shown that diclofenac itself can attenuate paininduced changes in BBB transporter activity (6). Our data suggest that a modulation in post-operative meperidine efficacy may, in part, be the result of altered CNS opioid delivery induced by diclofenac.…”
Section: Dear Editormentioning
confidence: 99%